Corrupting Luxury in Ancient Greek Literature - Gorman, Robert (Robert Joseph); Gorman, Vanessa B., 1963- (Book collections on Project MUSE., 2014)
Traces the principle that luxury corrupts its possessor as seen through a millennium of Greek literature.